Implementation of Good Village Governance in the Village of Dauh Puri Kangin Village - SANCAYA, I Wayan Werasmana; SAPUTRA, Komang Adi Kurniawan (Community Services: Sustainability Development, 2024)
As a principle, governance is a system of rules, processes and behaviors that influence how power is exercised at different levels of government, especially in relation to openness, participation, accountability, effectiveness and coherence. Good governance contributes to various development goals due to internal changes in the way power is managed from conventional control and command by the state to new ways that are more networked and balanced with various stakeholders. Based on this statement, every organization needs to implement good governance and it is possible at the village government level. The importance of implementing village governance that leads to a good village governance system will also lead to efforts to improve and enhance the government management process so that performance will be better. To encourage the realization of good village governance, it is important to build good governance that is transformed into good village governance. This view leads to the argument that certain villages, which have not yet formed good village governance, will experience disorientation in the implementation of government, if the maturity of human resources and institutional institutions is not prepared. Corruption and abuse of authority are major issues in village governance. Therefore, the village government must be able to apply the principle of accountability in village financial management, where all village government activities must be accountable to the village community.